Optimizing Big Data Analytics in the Era of Digital Transformation - Sipra Barutu (Jurnal Komputer Indonesia (Ju-Komi), 2025)
Digital transformation requires organizations to manage large, diverse, and high-velocity data to support effective decision-making. Big Data Analytics (BDA) plays a strategic role in this process through its ability to transform raw data into valuable insights for organizations. This study aims to analyze strategies for optimizing BDA in the digital transformation era by emphasizing the integration of technology, information systems, and organizational capabilities. The research uses a qualitative descriptive approach through a literature review of journals, industry reports, and scientific publications from 2018 to 2025. The findings indicate that the success of BDA optimization is determined by three key synergies: (1) robust and scalable technology, (2) integrated and secure information systems, and (3) adaptive and innovative organizational capabilities. The integration of these three aspects enables organizations to enhance operational effectiveness, strengthen competitiveness, and accelerate the success of digital transformation. Therefore, optimizing BDA is not merely a matter of technological implementation but a comprehensive transformation of how organizations think, make decisions, and create value in the digital era.